A "couraça nova" da Vila de Melgaço : resultado de uma intervenção arqueológica na Praça da República - Almeida, Carlos A. Brochado de (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The archaeological intervention carried out at "Praça da República", in Melgaço village, uncovered the moat which reinforced the borough defence; the "new cuirass" foundations; and one of the "false breech walls" of the bastioned trace system. The moat was, probably, built throughout the 14th century. The "new cuirass" was certainly built in D. João II reign, during the 15th century. Both structures were operational until the "Acclamation Wars", 2nd half of the 17th century; time when the moat was heaped and built a "false breech", which joined the exterior rampart of the tenaille, in the meantime built on the western side of the village, in orderto protect it with artillery, from a eminent Castilian attack from the Galician side.